Optical Properties of Er3+-Doped CdIn2O4 and CdIn2O4 Crystals - Tae Hwan Bang; Jong Wuk Kang; Jin Jeong (Journal of Spectroscopy)
CdIn2O4 and CdIn2O4:Er3+ crystals were grown by solid-state sintering of CdO and In2O3 with ErCl3. X-ray diffraction analysis revealed that CdIn2O4 and CdIn2O4:Er3+ adopt a cubic structure with respective lattice constants of a=9.1655 Å and a=9.1662 Å. The optical absorption spectra obtained near the fundamental absorption edge showed that these compounds have a direct energy band gap. The photoluminescence (PL) spectra of CdIn2O4:Er3+ acquired in the wavelength range of 630–700 nm at 294 K showed peaks in the region of 651–686 nm and eight sharp emission peaks due to the Er3+ ions. These PL peaks were attributed to radiative transitions between the split electron energy levels of the Er3+ ions occupying the In3+ sites of the CdIn2O4 host lattice.